Insertional Mutagenesis Strategies in Cancer Genetics - Dupuy, Adam J.; Largaespada, David A.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Over the past decades, insertional mutagenesis has played an important contribution to our understanding of cancer. Initially, the action of slow transforming retroviruses was used to identify endogenous cellular oncogenes (e.g. Myc, Myb). These observations sparked a series of experiments that eventually led to the idea cancer is caused by somatically acquired mutations in endogenous oncogenes and tumor suppressor genes. Since these discoveries, insertional mutagenesis has been used to identify novel cancer genes in a variety of tumor types in animal models of cancer. More recent work has developed novel insertional mutagens, such as transposons, that have broader capabilities to model cancer in vivo. While this work has focused on developing animal models of cancer, recent gene therapy trials in human patients have shown that insertional mutagenesis can also contribute to transformation. The goal of this work is summarize the contribution that insertional mutagenesis has made to our understanding of cancer. A variety of insertional mutagens are presented that have been used to study a variety of tumor types in several model organisms. In addition, the impact of insertional mutagenesis in several gene therapy trials is discussed along with strategies to avoid such complications in future clinical trials.
Chapter 1: Introduction: Author: Anton Berns (Netherlands Cancer Institute) -- Chapter 2: Retroviral mutagenesis in mouse leukemia/lymphoma: Author: David Largaespada, Ph.D. (University of Minnesota) -- Chapter 3: MMTV models of breast cancer: Author: John Hilkens (NKI) -- Chapter 4: Retroviral mutagenesis in other organisms: Author: Michael Dvorak (Inst. Of Molecular Genetics, Prague, Czech Rep.) -- Chapter 5: Sleeping Beauty models of cancer: Author: Adam J. Dupuy, Ph.D. (University of Iowa) -- Chapter 6: Insertional mutagenesis in gene therapy patients: Author: David Williams, M.D. (Cincinnati Children$1 (Bs Hospital) -- Chapter 7: Bioinformatics of high throughput insertional mutagenesis: Author: Keiko Akagi (NCI-Frederick).s
Keywords: Medicine; Oncology; Human genetics; Toxicology; Biomedicine; Cancer Research; Human Genetics; Pharmacology/Toxicology.